(untitled) (Journal of Asian Development Studies, 2023)
In the present era of the Industry 4.0 revolution, digitalization has transformed the operations of businesses, organizations and the banking industry as well. The success of the banking industry can’t be determined without advancement in ICT and online banking services (ONBS). Hence, banks must acknowledge alterations in Consumer adoption behaviour for the survival and sustainability of business operations in this digital Industry 4.0 era. Therefore, the current study intends to explore the nexus between online-banking service quality (OBSQ), Consumer’s perceived value (CPV) of the service provision, and their post-adoption behaviour intentions (CPBI). This study employs a quantitative approach and cross-sectional design. Data is collected from 278 clients who avail of online banking services from Pakistani Banks through a structured questionnaire. Data is analyzed using SPSS and Hayes process macro to perform mediation regression analysis. Study findings supported the mediation of CPV in OBSQ and CPBI relation. This research contributes to both management and academia, as the induction of digital technology in banking services in Industry 4.0 is imperative to facilitate banking consumers. Management must know factors which influence Consumer’s behaviour and ultimately result in their long-term retention with the same bank.